1991
DOI: 10.1128/mcb.11.11.5571
|View full text |Cite
|
Sign up to set email alerts
|

U4 small nuclear RNA dissociates from a yeast spliceosome and does not participate in the subsequent splicing reaction.

Abstract: U4 and U6 small nuclear RNAs reside in a single ribonucleoprotein particle, and both are required for pre-mRNA splicing. The U4/U6 and U5 small nuclear ribonucleoproteins join Ul and U2 on the pre-mRNA during spliceosome assembly. Binding of U4 is then destabilized prior to or concomitant with the 5' cleavage-ligation. In order to test the role of U4 RNA, we isolated a functional spliceosome by using extracts prepared from yeast cells carrying a temperature-sensitive allele ofprp2 (rna2). The isolated prp2A sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
70
0
4

Year Published

1993
1993
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(77 citation statements)
references
References 32 publications
3
70
0
4
Order By: Relevance
“…No free U6 snRNP was found and very little amounts of U4/U6 snRNP and [U4/U6.U5] tri-snRNP were detected in this extract (compare fractions 6-8, 12-14 and 24-28 in Figures 7C and D, respectively). In contrast, the free U5 snRNP amount (fractions [16][17][18][19][20][21][22] was increased and a free U4 snRNP was found (fractions [8][9][10][11][12][13][14]. This particle has a reduced velocity compared to the U4/U6 snRNP and very probably derives from U4/U6 snRNP disruption.…”
Section: Immunodetectionmentioning
confidence: 88%
See 1 more Smart Citation
“…No free U6 snRNP was found and very little amounts of U4/U6 snRNP and [U4/U6.U5] tri-snRNP were detected in this extract (compare fractions 6-8, 12-14 and 24-28 in Figures 7C and D, respectively). In contrast, the free U5 snRNP amount (fractions [16][17][18][19][20][21][22] was increased and a free U4 snRNP was found (fractions [8][9][10][11][12][13][14]. This particle has a reduced velocity compared to the U4/U6 snRNP and very probably derives from U4/U6 snRNP disruption.…”
Section: Immunodetectionmentioning
confidence: 88%
“…Then, the simultaneous addition of the U4/U6 and the U5 snRNPs, probably as a tri-snRNP, leads to the formation of the spliceosome. In this complex, the U4/U6 base pairing is disrupted leading to an active structure that catalyzes the splicing reaction per se (12). In addition to the polypeptides found in purified snRNPs, proteins which are not integral components of these particles are also required for efficient splicing.…”
Section: Introductionmentioning
confidence: 99%
“…A yeast strain carrying the prp2-1 mutation 72 and a C-terminally TAP-tagged Snu17p was created as described in ref. 73.…”
Section: Methodsmentioning
confidence: 99%
“…To determine if some of the differences noted above between plant and human U6atac snRNAs were functionally silent, we tested them in the context of an in vivo suppression assay for U6atac snRNA+ We have previously shown that human U6atac snRNA compensatory mutants expressed in Chinese hamster ovary (CHO) cells can suppress the in vivo cryptic splicing phenotype of 59 splice site mutants of a U12-dependent intron (Incorvaia & Padgett, 1998)+ Starting with this suppressor snRNA, we tested the effect of the A-to-G difference at position 26 of plant U6atac+ This position appears to be homologous to the invariant A of the AGC motif found in U6 snRNAs (Brow & Guthrie, 1988) and in human U6atac snRNAs (Tarn & Steitz, 1996b)+ In yeast U6 snRNA, mutation of this position leads to defects in splicing, particularly in the second step (Fabrizio & Abelson, 1990;Madhani et al+, 1990)+ However, mutation of this residue in mammalian U6 snRNA had no effect using an in vivo suppression assay (Datta & Weiner, 1993)+ When the A 26-to-G mutation was introduced into the suppressor U6atac construct (Figs+ 8A and 9), full in vivo suppressor activity was maintained showing that G 26 is fully compatible with active U12-dependent splicing+ Note that both A 26 and G 26 can potentially base pair to U12 snRNA in slightly different registers (Figs+ 7 and 8A)+ Immediately following this (A/G)GC sequence is a region that can form an intramolecular stem-loop that is similar in size, position, and structure to a critical region of U6 snRNA+ Although the plant and human U6atac sequences differ by almost 50% in this region, the predicted structures are similar+ To demonstrate that the plant stem-loop could still be active in spite of these differences, we constructed a chimeric U6atac in which the plant stem-loop replaced the human stemloop+ The resulting construct was tested for activity in vivo using the same suppressor assay described above+ We found that, in the presence of a mutated human U4atac snRNA, this chimeric U6atac snRNA was active in vivo (Figs+ 8A and 9)+ This shows that the function of the plant intramolecular stem-loop structure is conserved+ These data also provide the first in vivo evidence for the predicted function of U4atac snRNA in U12-dependent splicing+ When Tarn and Steitz (1996b) identified U6atac and U4atac snRNAs in human nuclear extracts, they noted that the two snRNAs could adopt a base-paired structure analogous to that formed by U4 and U6 snRNAs+ In the case of U4/U6 snRNA, this structure appears to be required for splicing in vivo and in vitro (Wolff & Bindereif, 1992)+ The precise role of this structure is still unclear but it has been proposed that U4 snRNA acts as a chaperone to deliver the U6 snRNA to the nascent spliceosome in an inactive form (Guthrie & Patterson, 1988)+ Subsequently, through the action of ATP-dependent helicases (Raghunathan & Guthrie, 1998), the two snRNAs are separated and U6 goes on to form alternative base-pairing interactions with U2 and the intron 59 splice site whereas U4 appears to be destabilized from the spliceosome (Lamond et al+, 1988;Yean &...…”
Section: Functional Testing Of Nonconserved Elements Of U6atac Snrnamentioning
confidence: 99%